FROM SCREENS TO SCHOOLYARDS - A COMPARATIVE ANALYSIS OF DIGITAL AND PHYSICAL SCHOOL VIOLENCE IN LIGHT OF INTERNATIONAL CHILDREN’S RIGHTS STANDARDS (Child and Family in Contemporary Society, 2025)
This study explores the intersection between digital and physical school violence from a comparative legal perspective, examining how various jurisdictions and international human rights frameworks address this issue. Drawing on legal analysis, case law, policy reviews, and empirical data, the paper investigates the ways in which online abuse – such as cyberbullying, digital harassment, and doxing – fuels in-person conflicts, reinforcing cycles of violence and intimidation among students. The study evaluates national legislative approaches in countries across Europe, North America, Asia, Africa, and Latin America, identifying best practices and gaps in enforcement. Key legal challenges, such as jurisdictional limitations in regulating online bullying, the balance between disciplinary measures and children’s rights, and the role of digital platforms in combating school violence, are critically assessed. The research further situates these legal responses within international human rights instruments, including the UN Convention on the Rights of the Child, regional human rights conventions, and emerging jurisprudence from courts and treaty bodies. Findings indicate that while legal systems are increasingly recognizing the convergence of digital and physical violence, enforcement remains inconsistent, and protections for children are often fragmented. This article argues that legal frameworks across jurisdictions have yet to fully integrate digital and physical forms of school violence into a unified rights-based response, and concludes that effective protection of children requires comprehensive legal reforms grounded in international human rights standards.